IDENTIFIKASI DAN INTERVENSI GANGGUAN BELAJAR SPESIFIK PADA ANAK - Ellen Wijaya (Bahasa Indonesia, 2020)
Introduction: Education is part of a child's learning process to form cognitive abilities and a good personality. Children who are unable to involve thinking skills, sensory and motor integration systems, as well as verbal and non-verbal functions, will experience learning disorders. The inability to read (dyslexia), write (dysgraphia), or arithmetic (dyscalculia) forms the domain of specific learning disorder in children. Identification and intervention of such cases require the full cooperation of parents, medical personnel, and teachers. Case: A boy, seven years of age, had been having barrier in reading based on six months of observation by school teacher since first-grade elementary school. The child did not have health problems, growth and development were according to age, and was able to engage in social interaction both at school and home environment. The patient fulfilled the reading domain criteria of specific learning disorder based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Patients received adequate intervention and are now successfully in the second grade of elementary school with the advancement in reading skills. Conclusion: The importance of early identification, intervention, and long term follow up in children with a specific learning disorder to achieve optimal quality of life.